The inflammatory response of fish to helminth parasites - SAYYAF DEZFULI, Bahram; LUI, Alice; BOLDRINI, Paola; GIARI, Luisa; F. Pironi (Parasite, 2008)
Fish serve as a good model for studying vertebrate immune systems because they have a relatively simple system. Descriptions of histopathological effects of helminth parasites on fish are few and far between with limited observations made on the identification of the inflammatory cells involved in the host reaction. Recently, two cell types found within teleosts received a great deal of attention, namely mast cells and rodlet cells. Fish mast cells also known as eosinophilic granule cells, are morphologically and functionally similar to their mammalian counterparts. Acute tissue damage causes mast cells degranulation and the release of mediators of inflammation, whereas, an increase in the number of these cells is usually found in chronically inflamed tissues. Rodlet cells, however, are exclusive to fish and are characterized by a distinct cell cortex and conspicuous inclusions, called rodlets, which accounts for their name. Piscidin has also been encountered within rodlet cells. As important cell types within the immune system of fish, both mast cells and rodlet cells have been seen to increase in number in infected fish, notably at the sites of pathogen attachment or infection. The present survey will provide data from studies with the light microscope on the response of mast cells and rodlet cells in a range of fish species (Anguilla anguilla, Oncorhynchus mykiss, Salmo trutta, Coregonus lavaretus) infected with a range of different parasite genera including representatives from the Digenea, Cestoda, Nematoda and Acanthocephala.